REAL HARASSMENT, VIRTUAL ROBOTS? IMPLICATIONS OF ONLINE HARASSMENT GEARED AT VIRTUAL ASSISTANT BIA - Rodrigues, Beatrys; Peruzzo, André (AoIR Selected Papers of Internet Research, 2023)
The purpose of this article is to investigate emerging themes in YouTube’s comments on the "BIA’s New Responses Against Harassment" video campaign. In the video, Bradesco bank presents less subservient responses to verbal attacks and harassment frequently sent to the brand’s virtual assistant, BIA. However, the comments in the video suggest a negative reception of the campaign by the audience, which can help illuminate broader discussions on social and symbolic asymmetries in feminized work rendered invisible by technology. The comments help us to reflect on understandings of what constitutes the human in artificial intelligence and how does the harassment of this virtual chatbot relates to the harassment suffered by women in virtual settings. To critically analyze these texts, we have taken a semiotic analysis of the audiovisual campaign based on Peircean semiotics of extraction and conducted a qualitative content analysis on 200 comments with the highest number of likes on the official Youtube video of the campaign, collected through Youtube Data Tools. Grounding our article in feminist technology studies and critical algorithmic research, we show how the audience reflects on the contradictory understandings of the humans rendered invisible in technology and that changing the materiality/code of technology is not enough to affect systems of gendered oppression.